2022
DOI: 10.3389/fped.2022.959439
|View full text |Cite
|
Sign up to set email alerts
|

CLCA1 mediates the regulatory effect of IL-13 on pediatric asthma

Abstract: ObjectiveCLCA1 is a secreted protein with protease activity, and its expression is associated with inflammatory airway diseases. This study aimed to investigate the role of CLCA1 and IL-13 in pediatric asthma.MethodsIn asthmatic and healthy children, the correlation between CLCA1 expression and blood IL-4, and IL-13 levels were investigated by serological analyses such as RT-qPCR and ELISA. The effects on the activity and apoptosis of bronchial epithelial cells following IL-13 stimulation were explored in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In a mouse model of acute lung inflammation, a lack of CLCA1 resulted in leukocyte recruitment and reduced cytokine expression (Erickson et al, 2018). Macrophages were activated in vitro (Mishina et al, 2015) and are highly associated with IL-13 expression in childhood asthma (Xu et al, 2022). In ovarian cancer, the existence of intracellular chloride channels, volume regulation, and voltage-gating has been observed through experiments conducted both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of acute lung inflammation, a lack of CLCA1 resulted in leukocyte recruitment and reduced cytokine expression (Erickson et al, 2018). Macrophages were activated in vitro (Mishina et al, 2015) and are highly associated with IL-13 expression in childhood asthma (Xu et al, 2022). In ovarian cancer, the existence of intracellular chloride channels, volume regulation, and voltage-gating has been observed through experiments conducted both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that CLCA1 primarily participates in multiple respiratory disorders like asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis, pneumonia, and other related conditions (den Dekker et al, 2019;Higham et al, 2022). The regulation of airway mucus secretion is controlled by CLCA1 through TMEM16A (Patel et al, 2009;Centeio et al, 2021), while also facilitating the initiation and progression of asthma via its mediation of IL13 (Xu et al, 2022). Further analysis of the whole gene transcriptome of the lung showed that respiratory mucin CLCA1 and tightly connected, inflammation-related genes were differentially expressed in different asthma inflammatory phenotypes (Tan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CLCA1 modulates mucus dynamics and homeostasis in multiple environments, such as intestinal and respiratory epithelia. In this topic, Xu et al (18) investigated associations between CLCA1 expression and IL-13 levels, which is the main biomarker of airway and blood eosinophilia, a main characteristic of type 2 asthma (19). To this end, the authors designed a full "bench-to-bedside" experimental approach.…”
mentioning
confidence: 99%